Lethal thermal maximum temperature induces behavioral responses and protein expressions (Hsp70 and p53) in juvenile common carp (Cyprinus carpio Linnaeus) - Machado, Alex S.D.; Cardoso, Caroline M.; Sartorio, Priscila V.; Costa, Eudriano F.S.; Vignardi, Caroline P.; Hasue, Fábio M.; Viadanna, Pedro H.O. [UNESP]; Santos, Dayana M. [UNESP]; Yasumaru, Fanny A.; Marion, Camila; Gomes, Vicente; Ngan, Phan V. (My University, 2017)
Temperature is one of the most important environmental factors influencing aquatic organisms at different levels and drastic changes can cause adverse effects on individuals, populations and ecosystems. This study investigated the behavioral response to heating stress and the protein expression of Hsp70 and p53 in muscle, liver, gills and heart at lethal thermal maximum (LTMax) in juvenile of common carp, Cyprinus carpio. The fish, acclimated at 25 °C, were submitted to gradual and constant heating up to the LTMax. The results indicated that heating to lethal maximum temperature causes behavioral alterations from temperature of 32.8 °C. In general, the LTMax ranged from 38 to 39.8 °C and 38.8 °C was the temperature at which 50% of the fish reached the LTMax. There were increase of Hsp70 and p53 expression in all tissues analyzed at LTMax in comparison with the control group, indicating loss of functional structure of proteins and DNA damage in juvenile C. carpio. This study suggests that heating causes behavioral and protein expression alterations to the fish and these alterations could affect the geographical distributions and survivor of this species.
Keywords: Denatured proteins; DNA damage; Fish; Temperature